Mothering of nature : an ecofeminist analysis of capitalism and motherhood in Barbara kingsolver’s flight behaviour and prodigal summer - Izza Ismail (2015)
The chosen works of modern eco-fiction writer Barbara Kingsolver demonstrate a common theme of female characters battling with themselves in the face of nature. More specifically, these characters each possess the need to be validated by society as strong, independent individuals despite their social circumstances. Kingsolver’s depiction of the three central protagonists’ growth and development is set against the backdrop of them coming to terms with various aspects of the female consciousness that the nature around them evokes. Furthermore, they are inextricably linked by their roles as mothers or mother figures in the texts. This thesis will be an ecofeminist reading of Kingsolver’s novels Prodigal Summer and Flight Behavior while remaining in discussion with the works of Karen. J Warren, Maria Mies, Vandana Shiva, and essays by other ecofeminist writers. Through these texts, I will argue that an ecofeminist analysis of the capitalist economy as portrayed by Kingsolver and its gendered division of labour is required in discussions of mothering responsibilities in a family unit. This may thus offer critical insights on the pluralisms of motherhood, both in familial and natural contexts.